How Network Analysis Uncovers International Networks of Smuggling History: Criminals in Nagasaki, Japan circa 1667 - Hyeok Hweon Kang (Journal of Cultural Analytics)
This paper takes a network analytic approach to investigating crime in seventeenth-century Japan. In 1667, the Nagasaki magistrate’s office conducted the largest documented smuggling crackdown in Tokugawa Japan (1603–1867), busting a ring of 87 arms traffickers who had been shipping contraband to Chosŏn Korea (1392–1910). I use the office’s “criminal investigation records” (*hankachō* 犯科帳) to build a dataset of the 94 suspects from ten Japanese towns who were interrogated about their involvement at the time. Using a three-mode network (people, place, crime), the resulting graphs and statistics reveal a new geography of the crime in question: contrary to the conclusions of the original investigators and of modern-day historians who “closely read” their records, the digital analysis relocates the epicenter of the smuggling ring to be in Tsushima, not Hakata or Nagasaki, and its ringleader as a merchant named Komoda Kanzaemon, rather than Itō Kozaemon. Though various limitations are recognized, the case study demonstrates the utility of network analysis on early modern crime data in general and for archives built with criminal-investigative intent like the _hankachō_ in particular.